Study of wet torrefaction and anaerobic digestion of empty fruit bunches for bioenergy production - Aziz N.A.M.; Mohamed H.; Zainal B.S.; Abdullah R.A.; Rizal N.A.S.M.; Yu K.L.; Jamali N.S. (Institute of Physics, 2025)
In Malaysia, the palm oil industry generates vast amounts of solid and liquid waste, including empty fruit bunches (EFB) and palm oil mill effluent (POME). Finding efficient and environmentally friendly ways to manage and utilise this waste is crucial for sustainability. The research explores the utilisation of wet torrefaction in water for EFB, examining its impact on anaerobic digestion, specifically the dark fermentation (DF) process. The liquid product of torrefied EFB was further investigated as a substrate for biohydrogen production, employing innovative pre-treatment methods such as heat and acid on POME as the inoculum. This study focused on exploring the impact of temperature and holding time on the wet torrefaction of EFB prior to the dark fermentation process. Wet torrefaction was conducted at temperatures between 180 - 210C and EFB: water ratio of 1:20 for 10 - 30 min, resulting in a mass yield of 52 - 54% and a chemical oxygen demand (COD) of 19.7 - 25.4 g/L COD. The chosen conditions (210C for 30 min) demonstrated the lowest COD, validating the potential of torrefied liquid EFB for biohydrogen production. Dark fermentation was carried out at 37C for 5 days, exploring various inoculum pretreatment parameters, including heat (80C for 1 hr) and acid treatment (HCL pH 2-4). Liquid torrefied EFB with heat treatment inoculum exhibited the highest biohydrogen yield of 5.8 Nml, a notable 18% increase compared to the control. Through optimisation of parameters and effective waste management strategies, wet torrefaction and dark fermentation of EFB and POME emerge as promising approaches for sustainable biomass utilisation and renewable energy generation. ? Published under licence by IOP Publishing Ltd.